Can The Subaltern Tweet? Reflections on Twitter as a Space of Appearance and Inequality in Accessing Visibility. (15th February 2018) - Trillò, Tommaso
ABSTRACT: Defining contemporary social movements as 'Twitter revolutions' has become increasingly common. A wide array of studies, however, suggest that social media and political participation have a complex relationship that cannot be reduced to easily intelligible causal links. Based on Gerbaudo's choreography of assembly and Butler's performative theory of assembly, this paper will firstly explore the case in favor of an understanding of Twitter as a place where people can perform their political claims and enact resistance. Based on Fuchs' asymmetrical political attention economy of capitalism, this paper will then put forward the argument that inequality in access to visibility substantially hinders Twitter's potential as a space for political engagement. Based on this framework, this paper will finally offer a short review of two recent cases of Twitter activism, and namely the Ni Una Menos feminist movement in Argentina and the Rhodes Must Fall/Fees Must Fall student movement in South Africa.